2013
DOI: 10.2138/am.2013.4319
|View full text |Cite
|
Sign up to set email alerts
|

Noise of collapsing minerals: Predictability of the compressional failure in goethite mines

Abstract: Compression experiments of goethite samples from an iron ore mine in New Caledonia revealed the collapse of the porous samples to follow a power law behavior. The porosity varies between 54 and 84%. The collapse under compression occurs in a series of individual events (avalanches). Each avalanche leads to a jerk in sample compression and an equivalent acoustic emission signal. The probability to find an acoustic emission signal with an energy within E and E + dE is p(E)dE, which has a power law distribution p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
39
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 53 publications
5
39
0
Order By: Relevance
“…Experimentally, it has been shown that the avalanches stem from sudden changes of the internal strain field (displacement discontinuities), which usually lead to shrinking of the sample and can be detected by measuring the acoustic emission (AE) originating from contraction. Avalanche behavior has been observed previously in porous Vycor glass [10], natural goethite [11], porous alumina [12], and berlinite [13]. Their statistical characteristics share many similarities with seismicity such as the Earth crust failure due to stresses originated from plate tectonics [14,15].…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…Experimentally, it has been shown that the avalanches stem from sudden changes of the internal strain field (displacement discontinuities), which usually lead to shrinking of the sample and can be detected by measuring the acoustic emission (AE) originating from contraction. Avalanche behavior has been observed previously in porous Vycor glass [10], natural goethite [11], porous alumina [12], and berlinite [13]. Their statistical characteristics share many similarities with seismicity such as the Earth crust failure due to stresses originated from plate tectonics [14,15].…”
Section: Introductionmentioning
confidence: 68%
“…Nevertheless, the corroboration of this hypothesis certainly requires more detailed investigations. The behavior in SiO 2 -porous materials is different from other porous materials such as goethite [11], berlinite [13], or alumina [12], which are also granular materials.…”
Section: Discussionmentioning
confidence: 93%
“…The experimental arrangement for a uniaxial compression has been described in detail in [2,27]. Each studied sample was placed between two parallel circular stainless steel plates, perpendicular to the direction of the applied force.…”
Section: B Compression Equipmentmentioning
confidence: 99%
“…This is the same approach as has been recently taken to study the failure of natural minerals such as goethite [27] and different sandstones [5] and some synthetic porous glasses such as Vycor and Gelsil [5] and alumina [28].…”
Section: Introductionmentioning
confidence: 99%
“…As failure is approached, temporal correlation of events emerges accompanied by spatial clustering. DOI: 10.1103/PhysRevLett.112.065501 PACS numbers: 61.43.Gt, 46.50.+a, 89.75.Da, 91.60.Ba Understanding the processes that lead to catastrophic failure of porous granular media is an important problem in a wide variety of applications, notably in Earth science and engineering [1][2][3][4][5][6][7][8]. Such failure is often preceded by detectable changes in mechanical properties (stress and strain) and in geophysical signals (elastic wave velocity, electrical conductivity, and acoustic emissions) measured remotely at the sample boundary [9].…”
mentioning
confidence: 99%